A good sign for multivariate risk taking - Louis Eeckhoudt; Béatrice Rey; Harris Schlesinger (Center for Economic Studies and ifo Institute (CESifo), 2006)
Decisions under risk are often multidimensional, where the preferences of the decision maker depend on several attributes. For example, an individual might be concerned about both her level of wealth and the condition of her health. Many times the signs of successive cross derivatives of a utility function play an important role in these models. However, there has not been a simple and intuitive interpretation for the meaning of such derivatives. The purpose of this paper is to give such an interpretation. In particular, we provide an equivalence between the signs of these cross derivatives and individual preference within a particular class of simple lotteries.
Keywords: D81; 330; Entscheidung bei Risiko; Multivariate Analyse; Operations Research